Managing today's news media audience first - Husni, Samir; Wenger, Debora Halpern; Price, Hank (CQ Press, and imprint of SAGE Publications, Inc., 2016)
Offers students practical solutions on how to cope with and adapt to the evolving media landscape. This book includes real-world case studies, important theoretical grounding, and a focus on understanding rather than resisting the customer's desire for choice.